Constructing Urban Lifestyle Through Billboard Advertising: A Case Study In Yogyakarta - Cut Irna Liyana; Irwan Abdullah; Sajarwa Sajarwa (Jurnal Community, 2021)
Advertising has an effect on changing lifestyles in urban communities. The massive development of billboard advertising in Indonesia's urban areas makes people exposed to advertising content every day. By using vocabulary and visualizing, directly or implicitly, advertising conveys messages and meanings that have an effect on the evolving lifestyles of urban populations. This paper would highlight how the language of advertising creates urban lifestyles in Yogyakarta by researching how advertising language building transmits a message and advertising language builds a lifestyle with an ideological orientation. It is also intended to support the target audience. This is qualitative analysis and data collection was carried out through observation and recording of the billboard advertising in Yogyakarta. Data was analyzed using the multimodal discourse analysis method of Gunter Kress and Theo van Leeuwen. The results indicate that billboard advertisements not only offer the commodity, but also convey the message of urban lifestyle directly and indirectly. Urban lifestyles are built using semiotic modes; language (using code mixing and foreign language) and visualization (using icon, image and color); in billboard advertising. They as well constructed ideologies that have structured society horizontally and vertically.Keywords: